Reprogramming barriers in bovine cells nuclear transfer revealed by single‐cell RNA‐seq analysis. Issue 18 (15th August 2022) - Zhao, Lixia; Long, Chunshen; Zhao, Gaoping; Su, Jie; Ren, Jie; Sun, Wei; Wang, Zixin; Zhang, Jia; Liu, Moning; Hao, Chunxia; Li, Hanshuang; Cao, Guifang; et al.
Abstract: Many progresses have recently been achieved in animal somatic cell nuclear transfer (SCNT). However, embryos derived from SCNT rarely result in live births. Single‐cell RNA sequencing (scRNA‐seq) can be used to investigate the development details of SCNT embryos. Here, bovine fibroblasts and three factors bovine iPSCs (3F biPSCs) were used as donors for bovine nuclear transfer, and the single blastomere transcriptome was analysed by scRNA‐seq. Compared to in vitro fertilization (IVF) embryos, SCNT embryos exhibited many defects. Abnormally expressed genes were found at each stage of embryos, which enriched in metabolism, and epigenetic modification. The DEGs of the adjacent stage in SCNT embryos did not follow the temporal expression pattern similar to that of IVF embryos. Particularly, SCNT 8‐cell stage embryos showed failures in some gene activation, including ZSCAN4, and defects in protein association networks which cored as POLR2K, GRO1, and ANKRD1. Some important signalling pathways also showed incomplete activation at SCNT zygote to morula stage. Interestingly, 3F biPSCNT embryos exhibited more dysregulated genes than SCNT embryos at zygote and 2‐cell stage, including genes in KDM family. Pseudotime analysis of 3F biPSCNT embryos showed the different developmental fate from SCNT and IVF embryos. These findings suggested partial reprogrammed 3F biPS cells as donors for bovine nuclear transfer hindered the reprogramming of nuclear transfer embryos. Our studies revealed the abnormal gene expression and pathway activation of SCNT embryos, which could increase our understanding of the development of SCNT embryos and give hints to improve the efficiency of nuclear transfer.